Pengembangan Media Belajar Peti Ice Pada Pembelajaran Tematik Siswa Kelas 3 Sekolah Dasar - Aditya Rachman; Muhammad Hidayat (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This research covers the process of developing and evaluating ICE Crate learning media in depth. This problem focuses on the stages of development, design, implementation, and measurement of the effectiveness of these learning media in improving the learning outcomes of grade 3 students in thematic learning. Through the PETI ICE learning media (Innovative Cycle Life and Decorative Thematic Learning), students are expected to be able to experience innovative learning. This study aims to improve student learning outcomes in thematic learning and describe the increase in student learning outcomes in thematic learning. The research methodology is classroom action research (CAR). The model in this study uses the Kemmis and Taggart implementation flow and the researchers use the R & D approach (research and development). The utilization of innovative media